How To Make Nitroaromatic Compounds Glow: Next‐Generation Large X‐Shaped, Centrosymmetric Diketopyrrolopyrroles. (10th July 2020) - Skonieczny, Kamil; Papadopoulos, Ilias; Thiel, Dominik; Gutkowski, Krzysztof; Haines, Philipp; McCosker, Patrick M.; Laurent, Adèle D.; Keller, Paul A.; Clark, Timothy; Jacquemin, Denis; Guldi, Dirk M.; Gryko, Daniel T.
Abstract: Red‐emissive π‐expanded diketopyrrolopyrroles (DPPs) with fluorescence reaching λ=750 nm can be easily synthesized by a three‐step strategy involving the preparation of diketopyrrolopyrrole followed by N‐arylation and subsequent intramolecular palladium‐catalyzed direct arylation. Comprehensive spectroscopic assays combined with first‐principles calculations corroborated that both N‐arylated and fused DPPs reach a locally excited (S1 ) state after excitation, followed by internal conversion to states with solvent and structural relaxation, before eventually undergoing intersystem crossing. Only the structurally relaxed state is fluorescent, with lifetimes in the range of several nanoseconds and tens of picoseconds in nonpolar and polar solvents, respectively. The lifetimes correlate with the fluorescence quantum yields, which range from 6 % to 88 % in nonpolar solvents and from 0.4 % and 3.2 % in polar solvents. A very inefficient (T1 ) population is responsible for fluorescence quantum yields as high as 88 % for the fully fused DPP in polar solvents. Abstract : Go with the glow : A two‐step process has been developed that transforms parent diketopyrrolopyrrole into structures with up to 10 fused rings. The absorptions are bathochromically shifted to the deep‐red region and strong red emission is seen, even in nonpolar solvents, despite the presence of NO2 groups.